A genome-wide association study using a Vietnamese landrace panel of rice (Oryza sativa) reveals new QTLs controlling panicle morphological traits - TA, Kim Nhung (BMC Plant Biol, 2018)
CONTEXT: Yield improvement is an important issue for rice breeding. Panicle architecture is one of the key components of rice yield and exhibits a large diversity. To identify the morphological and genetic determinants of panicle architecture, we performed a detailed phenotypic analysis and a genome-wide association study (GWAS) using an original panel of Vietnamese landraces. RESULTS: Using a newly developed image analysis tool, morphological traits of the panicles were scored over two years: rachis length; primary, secondary and tertiary branch number; average length of primary and secondary branches; average length of internode on rachis and primary branch. We observed a high contribution of spikelet number and secondary branch number per panicle to the overall phenotypic diversity in the dataset. Twenty-nine stable QTLs associated with seven traits were detected through GWAS over the two years. Some of these QTLs were associated with genes already implicated in panicle development. Importantly, the present study revealed the existence of new QTLs associated with the spikelet number, secondary branch number and primary branch number traits. CONCLUSIONS: Our phenotypic analysis of panicle architecture variation suggests that with the panel of samples used, morphological diversity depends largely on the balance between indeterminate vs. determinate axillary meristem fate on primary branches, supporting the notion of differences in axillary meristem fate between rachis and primary branches. Our genome-wide association study led to the identification of numerous genomic sites covering all the traits studied and will be of interest for breeding programs aimed at improving yield. The new QTLs detected in this study provide a basis for the identification of new genes controlling panicle development and yield in rice. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12870-018-1504-1) contains supplementary material, which is available to authorized users.